Bioseparation of alpha-amylase by forming insoluble complexes with - Porfiri, María Cecilia (2012)
Precipitation of insoluble complexes between alpha-amylase from Aspergillus oryzae and polyacrylic acid was studied by us in a previous work as a strategy of protein concentration and purification. Here we studied the effect of these polyelectrolytes on the stability of the enzyme at the pH of higher interaction (3.00), as well as the stability of the precipitates formed after applied the above methodology. The polymers showed a stabilizing effect on the activity of alpha-amylase at pH 3.00, intensified when complexes are in the solid precipitated form before redissolve. In a subsequent step, a strain of Aspergillus oryzae was used as enzymatic source. In order to stimulate alpha-amylase production and secretion by the microorganism, we used a minimum culture medium with wheat processing residues as substrate. This has economic and environmental benefits, because of the recycling of agricultural wastes. When the technique of concentration and purification of alpha-amylase was implemented from these cultures we obtained satisfactory results, which demonstrate that this methodology is suitable for the concentration and purification of alpha-amylase from A. oryzae in an inexpensive way, since it uses agricultural materials without commercial value.